Efficacy and safety of front-line treatments for advanced Hodgkin lymphoma: a systematic literature review. Issue 8 (2nd August 2020) - Dalal, Mehul; Gupta, Jatin; Price, Kim; Zomas, Athanasios; Miao, Harry; Ashaye, Ajibade
ABSTRACT: Objective: To assess evidence on the safety and efficacy of ABVD (doxorubicin [Adriamycin®], bleomycin, vinblastine, and dacarbazine), BEACOPP (bleomycin, etoposide, doxorubicin, cyclophosphamide, vincristine, procarbazine, and prednisone), and A+AVD (brentuximab vedotin, with doxorubicin, vinblastine, and dacarbazine) for advanced-stage Hodgkin lymphoma (HL). Methods: A systematic literature review (SLR) was conducted on 29 July 2016 (updated 26 July 2018) to identify randomized controlled trials (RCTs) and non-RCTs assessing the treatment of newly-diagnosed advanced-stage HL with ABVD and BEACOPP (and their variants), and A+AVD. Results: The SLR identified 62 RCTs and 42 non-RCTs. Five-year overall survival rates for ABVD and BEACOPP were 60–97% and 84–99%, and 5-year progression-free survival rates were 58–81% and 83–96%, respectively. Both regimens were associated with tolerability issues and side effects. Discontinuation or dose reduction of bleomycin resulted in fewer adverse events, without significantly affecting efficacy. A head-to-head trial demonstrated improved efficacy for A+AVD vs ABVD, with an acceptable tolerability profile. No data from head-to-head trials comparing A+AVD with BEACOPP were available, and an indirect treatment comparison was not feasible. Conclusion: New therapies, such as A+AVD, maintain the efficacy observed with current treatments, and may provide a more tolerable treatment option for patients with advanced-stage HL.